Emulation encounters: Software preservation in libraries, archives, and museums. Issue 1 (22nd October 2020) - Acker, Amelia
Abstract: This paper reports on early findings of research in 2019 following three small teams of information professionals as they implemented emulation strategies into their day‐to‐day work at a museum, a university research library, and a university research archive and technology lab. Findings are reported from workplace observations and semi‐structured interviews with preservationists (N = 25) as they implement software emulation programs in cultural heritage institutions that collect and preserve software for access. Results suggest that the distributed teams in this cohort of preservationists have developed different emulation practices for particular kinds of "emulation encounters" in supporting different types of use and users. I discuss the implications of these findings for digital preservation research and emulation initiatives providing access to software or software‐dependent objects, showing how implications of these findings have significance for those developing software preservation workflows and building emulation capacities. This article suggests that there are different emulation practices for preservation, research access, and exhibition undertaken by preservationists in libraries, archives, and museums; and in examining particular visions of access these findings call into question software emulation as a single, static preservation strategy for cultural heritage institutions.